Model Collaborative Dalam Sosialisasi Bijak Bersosial Media Dan Bahaya Merokok Pada Anak di SD Negeri 06 Ciputat Tangerang Selatan - Primanda, Debi; Nur Azizah, Erlina; Azkia Hanum, Farriha; Mubarak Keliobas, Faizal; Amaral Fiscal, Muhammad; Himayatun, Az Zahra; Sobariyah, Siti; Fadel, Fadel (CV RIFAINSTITUT, 2023)
Social media is social interaction between people sharing and exchanging information. Social media can contain various ideas, opinions, ideas and content in virtual communities and is able to represent and translate new ways of communicating using technology that is completely different from traditional media. In the global era, the development of increasingly innovative technology has directly affected society, especially the younger generation. Owners can access social media anytime, anywhere via smartphone.In teaching and education, distinguished between externalization (secret content), objectification (become reality) and internalization of this reality. Smoking behavior is a person’s response to external stimuli that cause the person to smoke and can be observed directly. Smoking behavior has been rife in Indonesian society, especially among local people.The research method used in this research is descriptive research with a qualitative approach. Qualitative research focuses on social phenomena that express the feelings and perceptions of those being studied. Data collection techniques are carried out through outreach, observation and documentation. Then the research data obtained were analyzed in stages, namely. H. Data reduction, presentation and conclusion.The collaborative management model in the context of smart socialization and education on social media and the dangers of smoking at SDN Ciputat 06 Kota Tangerang Selatan uses the concepts and theories of Ansell and Gash.